10.- Max Z = 2X1 + 4X2 + X3
S.a.
X1 + 2X2 – X3 ≤ 5
2X1 – X2 + 2X3 = 2
-X1 + 2X2 + 2X3 ≥ 1
X1 , X2 , X3 ≥ 0
Forma Estandarizada :
Max Z = 2X1 + 4X2 + X3 + 0S1 + 0S3 – MA2 – MA3
S.a.
X1 + 2X2 – X3 + S1 = 5
2X1 – X2 + 2X3 + A2 = 2
-X1 + 2X2 + 2X3 - S3 + A3 = 1
| | CJ | 2 | 4 | 1 | 0 | 0 | -M | -M | |
CB | XB | bI | X1 | X2 | X3 | S3 | S1 | A1 | A2 | θ K |
0 | S1 | 5 | 1 | 2 | -1 | 0 | 1 | 0 | 0 | - |
-M | A1 | 2 | 2 | -1 | 2 | 0 | 0 | 1 | 0 | 1 |
-M | A2 | 1 | -1 | 2 | 2 | -1 | 0 | 0 | 1 | 1/2 |
| ZJ | -3M | -M | -M | -4M | M | 0 | -M | -M | |
| ZJ + | CJ | -M - 2 | -M - 4 | -4M - 1 | -M | 0 | 0 | 0 | |
0 | S1 | 11/2 | 1/2 | 3 | 0 | -1/2 | 1 | 0 | 1/2 | 11 |
-M | A1 | 1 | 3 | -3 | 0 | 1 | 0 | 1 | -1 | 1/3 |
1 | X3 | 1/2 | -1/2 | 1 | 1 | -1/2 | 0 | 0 | 1/2 | - |
| ZJ | -M +1/2 | -3M-1/2 | 3M+1 | 1 | -M-1/2 | 0 | -M | M+1/2 | |
| ZJ + | CJ | -3M-5/2 | 3M-3 | 0 | -M-1/2 | 0 | 0 | 2M+1/2 | |
0 | S1 | 16/3 | 0 | 7/2 | 0 | -2/3 | 1 | -1/6 | 2/3 | 32/21 |
2 | X1 | 1/3 | 1 | -1 | 0 | 1/3 | 0 | 1/3 | -1/3 | - |
1 | X3 | 2/3 | 0 | 1/2 | 1 | -1/3 | 0 | 1/6 | 1/3 | 4/3 |
| ZJ | 4/3 | 2 | -3/2 | 1 | 1/3 | 0 | 5/6 | -1/3 | |
| ZJ + | CJ | 0 | -11/2 | 0 | 1/3 | 0 | M + 5/6 | M – 1/3 | |
0 | S1 | 2/3 | 0 | 0 | -7 | 5/3 | 1 | -4/3 | -5/3 | 2/5 |
2 | X1 | 5/3 | 1 | 0 | 2 | -1/3 | 0 | 2/3 | 1/3 | - |
4 | X2 | 4/3 | 0 | 1 | 2 | -2/3 | 0 | 1/3 | 2/3 | - |
| ZJ | 26/3 | 2 | 4 | 12 | -10/3 | 0 | 8/3 | 10/3 | |
| ZJ + | CJ | 0 | 0 | 11 | -10/3 | 0 | M + 8/3 | M + 10/3 | |
0 | S3 | 2/5 | 0 | 0 | -21/5 | 1 | -3/5 | -4/5 | -1 | - |
2 | X1 | 9/5 | 1 | 0 | 3/5 | 0 | 1/5 | 2/5 | 0 | 3 |
4 | X2 | 8/5 | 0 | 1 | -4/5 | 0 | 2/5 | -1/5 | 0 | - |
| ZJ | 10 | 2 | 4 | -2 | 0 | 2 | 0 | 0 | |
| ZJ + | CJ | 0 | 0 | -3 | 0 | 2 | M | M | |
0 | S3 | 13 | 7 | 0 | 0 | 8 | 2 | 2 | -8 | |
1 | X3 | 3 | 5/3 | 0 | 1 | 0 | 1/3 | 2/3 | 0 | |
4 | X2 | 4 | 4/3 | 1 | 0 | 0 | 2/3 | 1/3 | 0 | |
| ZJ | 19 | 7 | 4 | 1 | 0 | 3 | 2 | 0 | |
| ZJ + | CJ | 5 | 0 | 0 | 0 | 3 | M + 2 | M | |
X2 = 4 X3 = 3 S3 = 13 Z = 19
Max Z = 2(0) + 4(4) + 1(3) + 0(S1) + 0(13) – M(0) – M(0) = 19
Max Z = 19
11.-Max X = X1 + 2X2
S.a.
X1 – 4X2 ≤ 1
-3X1 + 2X2 ≤ 6
X1 , X2 ≥ 0
Forma Estandarizada:
Max Z = X1 + 2X2 + 0S1 + 0S2
S.a.
X1 – 4X2 +0S1 = 1
-3X1 +2X2 +0S2 = 6
X1 , X2 , S1 , S2 ≥ 0
| | CJ | 1 | 2 | 0 | 0 | |
CB | XB | bi | X1 | X2 | S1 | S2 | θ K |
0 | S1 | 1 | 1 | -4 | 1 | 0 | - |
0 | S2 | 6 | -3 | 2 | 0 | 1 | 3 |
| ZJ | 0 | 0 | 0 | 0 | 0 | |
| ZJ + | CJ | -1 | -2 | 0 | 0 | |
0 | S1 | 13 | -5 | 0 | 1 | 2 | - |
2 | X2 | 3 | -3/2 | 1 | 0 | 1/2 | - |
| ZJ | 6 | -3 | 2 | 0 | 1 | |
| ZJ + | CJ | -4 | 0 | 0 | 1 | |
No hay comentarios:
Publicar un comentario